Diffusion Innovations of the Ministry of Social Affairs of the Republic of Indonesia in Disseminating Innovation of the E-Warong Program - Nadya Caesarany; Garry Vardy Karwur; Devia Rosalina (DIII Prodi Humas Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2019)
This research aims to find out and to depict the public relations activities in spreading the information of E-Warong program, as well as to discover the obstacles in running the aforementioned public relations activities. A descriptive-qualitative method is used to depict and to describe the examined objects according to the real facts in the field by using interviewees as the source of data. The data is presented using primary and secondary data through in-depth interview, documentation of activities, references related to the research, and data from the internet. The data analysis procedure used is qualitative data with interactive model from Metthew B. Miles and Michael Huberman. The results show that the public relations activities performed by the public relations team of the Ministry of Social Services in spreading the information include the following steps: 1) planning and decision-making in spreading the information of the E-Warong Program; 2) informing and performing the information spreading of E-Warong Program; 3) evaluating the performed information-spreading activity of E-Warong Program. Less appropriate selection of the communication channel for target audiences can be an obstacle faced during the means of information spreading of the E-Warong Program. In the end, the information spreading activity performed by the Ministry of Social Services ran well enough even though there were some flaws in the execution. Keywords: Public Relations activities, Spreading the Information